Building Labor Solidarity in Precarious Times: The Danger of Union Paternalism. (December 2019) - Paret, Marcel
In a global context of union decline and widening economic insecurity, unions must decide how to relate to extra-workplace struggles and those without stable or unionized employment. One possibility is that unions will adopt a paternalistic view, in which they attempt to serve the interests of nonunion individuals and groups by disciplining them or speaking for them. Drawing on seventy-five brief interviews with participants in a protest led by the Congress of South African Trade Unions (COSATU), I examine how union activists understood their relationship to the unemployed and local protests within residential areas. Revealing support for union involvement in extra-workplace struggles, the results show that South Africa's legacy of social movement unionism remains strong. Yet, some union activists also wanted to discipline or substitute for community struggles, and felt the need to educate or speak for the unemployed. Such paternalistic views may become an obstacle to broad working-class solidarity, in South Africa or elsewhere.